Flow Diversion for the Treatment of Middle Cerebral Artery Aneurysms - Schüngel, Marie-Sophie; Wohlgemuth, Walter A; Elolf, Erck; Rensch, Leonhard; Brill, Richard; Schob, Stefan (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
The invention of flow diverting stents (FDS) is a novel milestone in the field of endovascular aneurysm therapy, promoting physiological healing of the vessel segment contrary to prior deconstructive treatment strategies, such as coiling. The effects of FDS are based on changes in flow patterns, segmental wall stabilization, and the growth of a neointima. Although flow diversion is already well established for cerebral aneurysms in proximal segments, peripheral locations remain challenging. Especially the middle cerebral artery (MCA) with its predominance of non-collateralized perforators and functional end arteries that supply the eloquent areas of the brain is of major concern.The literature was reviewed for flow diversion of the MCA and antiplatelet therapy.Resulting from the special anatomical characteristics of the MCA, FDS implantation in this territory is completely different from the proximal vessel segments. Still, flow diversion represents an effective endovascular strategy, especially in otherwise non-accessible or sufficiently treatable lesions. However, the risk of ischemic adverse events might be increased. Special attention to the individual decision regarding device selection, antiplatelet regimen, and exact definition of the proximal and distal landing zone considering the jailed side branches is essential for a good angiographic and clinical outcome.
Keywords: aneurysm; middle cerebral artery; antiplatelet therapy